Kekuatan Pembuktian Visum Et Repertum Dalam Tindak Pidana Pembunuhan Berencana Berdasarkan Analisis Putusan Mahkamah Agung Nomor 2223 K/Pid/2010 - Maulana, Rifqy (Jurnal Ilmiah Wahana Pendidikan, 2024)
Visum et repertum comes from the Latin words translated into English, namely something seen or appearance (visum) and inventions or find out (repertum). According to the term, visum et repertum means a written report made by a doctor based on his oath of office regarding what the doctor saw and examined based on his knowledge. One of the cases that is difficult to prove is a murder case, this is because many murder cases are committed in quiet places so there are rarely any live witnesses so a Visum et Repertum is needed on the corpse to find out what really happened. If detailed according to the articles in the Criminal Code, criminal acts or cases that require a Visum et Repertum include, among others, murder with a plan (moord) including murder of children with a plan (kinder moord) and suicide (self- moord) is contained in Articles 340, 342 and 345 of the Criminal Code Premeditated crime is regulated in Article 340 of the Criminal Code which reads as follows: "Anyone who deliberately and with premeditation takes the life of another person, is threatened with premeditated murder, with the death penalty or life imprisonment or imprisonment for a maximum period of twenty years.”